If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + -40 = 20 Reorder the terms: -40 + -4y = 20 Solving -40 + -4y = 20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + -4y = 20 + 40 Combine like terms: -40 + 40 = 0 0 + -4y = 20 + 40 -4y = 20 + 40 Combine like terms: 20 + 40 = 60 -4y = 60 Divide each side by '-4'. y = -15 Simplifying y = -15
| 2x+6=7x-11 | | 2(2x+6)-3(x-4)=21 | | 17x+117= | | 530.66=3.14*r*r | | 8+4x=90 | | -6+a=7 | | 2(5x-6y)-(2x+3y)= | | (15x+15)+5x= | | 530.66=3.14*r*2 | | 4x+-7=-24 | | 13x+y=9 | | 8n(n-2)=5 | | 17/25=x/18 | | -6+b=52 | | 5x-4y=-25 | | x+x-4+x-4*2=68 | | 16x^2-64x-4=0 | | 2.3(x)^(1/2) | | sin^2(2x)+3sin(2x)-2=0 | | 10x^2+20x-45=8 | | 6x^2-20x-154=0 | | 7-4(x+6)= | | 4t-1=-3(3t-4) | | 12=-2y | | X/-x-90=0 | | 3(2x)-9x-4=2x+12 | | 4x+x^2=-2.5 | | y=4.5(x-27) | | sin^2(pi/6) | | 2(5x-6y)-(2x+3y)=equation | | (b-9)(b+9)= | | 4x^2-15x+36=6x+9 |